PENGARUH BOARD DIVERSITY DAN BOARD EXPERTISE TERHADAP CORPORATE SUSTAINABILITY PERFORMANCE - Putri Pangesti (2023)
This study is quantitative research that aims to analyze the Influence of board of commissioners' gender diversity, top management team gender composition, board of directors' nationality diversity, and board expertise on corporate sustainability performance. This study also uses four control variables, namely firm size, leverage, firm age, and profitability. This study uses secondary data in the form of annual reports and company sustainability reports with a total of 135 samples non-financial sector companies listed on Indonesia Stock Exchange in period 2019-2021 and processed using STATA 14.2. The results of this study prove that board of commissioners' gender diversity has a significant and negative effect on economic sustainability performance. Board of commissioners' gender diversity has no significant on environment and social sustainability performance. top management team gender composition has a significant and positive effect on economic sustainability performance. Top management team gender composition has no significant on environment and social sustainability performance. Board of directors' nationality diversity has no significant on economic, environment, and social sustainability performance. Board expertise has a significant and negative effect on economic sustainability performance. Board expertise has no significant on environment and social sustainability performance.